Evaluation of Mediterranean Tree Leaves as Valuable Biomass of Digestive Enzymes and Bacterial Inhibitors in the Concept of Circular Bioeconomy - Christou, Atalanti; Stavrou, Konstantina; Michael, Christodoulos; Botsaris, George; Goulas, Vlasios (My University, 2024)
This study aspires to evaluate the antibacterial and inhibitory effects of carbohydrate digestive enzymes in tree leaves that are widely distributed in the Mediterranean region. Leaves were sequentially extracted with solvents of increasing polarity. The results demonstrated a wide range of phenolic (3.5–770.7 mg gallic acid equivalent g−1) and flavonoid (0.2–321.3 mg catechin equivalent g−1) contents in leaf extracts. The minimum inhibitory and bactericidal concentration of leaf extracts was determined for six bacteria using the broth microdilution method. The polar extracts of carob, lentisk, and white mulberry leaves exerted strong antibacterial potency against Gram-positive bacteria, while the susceptibility of Escherichia coli on relative apolar extracts of carob, fig, and olive leaves was also observed. In parallel, the inhibitory effects of leaf extracts on carbohydrate digestive enzymes were evaluated. A robust inhibition of α-glucosidase was found for carob and lentisk leaf extracts, followed by extracts produced by white mulberry and olive leaves. Carob and lentisk leaves also act as a-amylase inhibitors at high concentrations. Overall, this study provides valuable data for the nutraceutical value of the “forgotten” treasure of Mediterranean tree leaves and assesses these plants as potential sources of antibacterial and carbohydrate digestive enzyme inhibitory agents for drug discovery.
Keywords: agricultural residues; antidiabetic activity; antimicrobial activity; phenolic compounds; α-glucosidase; α-amylase